Biomineralization-inspired sandwich dentin desensitization strategy based on multifunctional nanocomposite with yolk–shell structure. Issue 1 (21st November 2022) - Yi, Luyao; Wu, Hongling; Xu, Yue; Yu, Jian; Zhao, Yaning; Yang, Hongye; Huang, Cui
Abstract : A novel biomineralization-inspired sandwich dentin desensitization strategy combining immediate and long-term occluding effects was mediated using a multifunctional yolk–shell nanocomposite. Abstract : Dentin hypersensitivity (DH) treatment is far from being unequivocal in providing a superior strategy that combines immediate and long-term efficiency of dentinal tubule (DT) occlusion and clinical applicability. In order to achieve this aim, a type of multifunctional yolk–shell nanocomposite with acid resistance, mechanical resistance and biomineralization properties was developed in this study, which consists of a silica/mesoporous titanium–zirconium nanocarrier (STZ) and poly(allylamine hydrochloride) (PAH)-stabilized amorphous calcium phosphate (ACP) liquid precursor. First, the nanocomposite, named as PSTZ, immediately occluded DTs and demonstrated outstanding acid and mechanical resistance. Second, the PSTZ nanocomposite induced intrafibrillar mineralization of single-layer collagen fibrils and remineralization of demineralized dentin matrix. Finally, PSTZ promoted the odontogenic differentiation of dental pulp stem cells by releasing ACP and silicon ions. The reconstruction of the dentin-mimicking hierarchical structure and the introduction of newly formed minerals in the upper, middle and lower segments of DTs, defined as sandwich-like structures, markedly reduced the permeability and achieved superior long-term sealing effects. The nanocomposite material based on mesoporous yolk–shell carriers and liquid-phase mineralized precursors developed in this study represents a versatile biomimetic sandwich desensitization strategy and offers fresh insight into the clinical management of DH.